الحاجات النفسية ودورها في إعادة التأهيل الحركي لدى المعاق حركيا في نظر أخصائيين التأهيل الحركي لبعض المراكز الخاصة(المسيلة) - بن قويدر ساعد; Supervisor د/جيلالي تمساوت (Mohamed Boudiaf University of M'sila, 2024)
الملخص: بالعربية (عبارة عن فقرة(: هدفت الدراسة إلى معرفة دور الحاجات النفسية لدى المعاقين حركيا واشتملت الدراسة على عينة قوامها (31) اخصائي ومعالجين تأهيل حركي على مستوي خمس مراكز (05 ) موزعين 03 مراكز بلدية سيدي عيسى ومركزين على مستوى المسيلة بعد تطبيق مقياس الحاجات النفسية من إعداد الباحث أسفرت النتائج مستوى درجة مساهمة الحاجات النفسية في إعادة التأهيل الحركي للمعاقين ، قيمة عالية، وبالتالي فإن هذه النتيجة تؤيد فرضية البحث العامة عنوان الدراسة: الحاجات النفسية ودورها في إعادة التأهيل الحركي لدى المعاق حركيا في نظر أخصائيين التأهيل الحركي لبعض المراكز الخاصة(المسيلة) أهداف الدراسة: 1-تهدف هذه الدراسة إلي معرفه أهم الحاجات النفسية التي يمكن اشباعها ودورها في اعادة التأهيل الحركي لدى المعاقين تحديد مستوى تأثير الحاجات النفسية في اعادة التأهيل الحركي لدى المعاق حركيا.2- 3- الكشف عن دور الحاجات النفسية في اعادة التأهيل الحركي لدى المعاق حركي 4 - معرفة الحاجات النفسية الأساسية للمعاق حركيا من أجل فهم سلوكه والتعامل معه بالطرق المناسبة 5- الاطلاع على الحاجات النفسية والعمل على تعزيزها من أجل رفع مستوى الاستجابة في اعادة التأهيل مشكلة الدراسة: ما دور الحاجات النفسية في إعادة التأهيل الحركي لدى المعاق حركيا؟ فرضيات الدراسة: أ-الفرضية العامة للحاجات النفسية دورا في اعادة التأهيل الحركي لدى المعاق حركيا. ب-الفرضيات الجزئية لحاجات الاستقلال دور في إعادة التأهيل الحر كي للمعاق حركيا -1 لحاجات الانتماء دور في إعادة التأهيل الحركي للمعاق حركيا-2 3- لحاجات الكفاءة دور في إعادة التأهيل الحركي للمعاق حركيا. المنهج المتبع في الدراسة: المنهج الوصفي الأدوات المستخدمة في الدراسة: استبيان السيكو مترية للحاجات النفسية كلمات المفتاحية -الحاجات النفسية - التأهيل الحركي - المعاق حركيا؟ Mots clès بالفرنسية : Le handicap moteur- Besoins psychologiques - rééducation Keywords. بالإنجليزية Rehabilitation - Motor disability - Psychological needs جاء هذا البحث في 7 فصول الفصل الأول: الجانب المنهجي وهو الإطار العام للبحث أما الفصل الثالث: الإعاقة الحركية. الحاجات النفسية وتناول الفصل الثاني : الفصل الرابع: التأهيل الحركي اما ا الفصل الخامس:ا لجانب التطبيقي منهجية الدراسة الفصل السادس: عر ض وتحليل ومناقشة النتائج الفصل السابع: استنتاجات والاقتراحات من أهم النتائج التي توصل إليها الباحث درجة حاجات الاستقلال في إعادة التأهيل الحركي للمعاقين عالية درجة حاجات الانتماء في إعادة التأهيل الحركي للمعاقين عالية -درجة الكفاءة في إعادة التأهيل الحركي للمعاقين عالية : توصل الباحث للعديد من التوصيات أهمها 1-العمل على وضع استراتيجيات تدريبية لتطوير البرامج الخاصة بمراحل التأهيل الحركي التوجيه والإرشاد، التدريب الحركي التشغيل المهني، المتابعة (وتنفيذها بشكل جيد في مراكز التأهيل الميني الكشف المبكر للحاجات النفسية للأفراد بصفة عامة لا سيما دوي الاحتياجات الخاصة-2 تذليل الصعوبات والمشكلات التي تقف خلف تحقيق أهداف برامج التأهيل الحركي للمعوقين في -3 جميع مراكز التأهيل الحركي في الجزائر - وضع خطة وطنية شاملة لتحقيق الاستفادة القصوى من مرا كز التأهيل الحركي بالنسبة للمعوقين 4 و أسرهم والمجتمع عامة الاهتمام بوضع برامج للمعاقين حركيا من المرحلة المبكرة من خلال تمارين النشاط الحركي -5 6-ااقتراح مواضيع مشابهة فيما يخص الحاجات النفسية لمتغيرات اخرى مشابهة لموضوعنا برامج كشاف بالإنجليزية Institute of Science and Technology of Physical Activity and Sports. Department Adapted sports physical activity Serial number: 23969615392023 Registration number: 23969615392023 Student benkouider saad Discussion date: 06/04/2024 Memo title. Psychological needs and their role in motor rehabilitation for the physically disabled In the opinion of motor rehabilitation specialists in some private centers (Msila) Language of memorandum: Arabic Note type: Master 2 Country: People's Democratic Republic of Algeria - M'Sila - University: Mohamed Boudiaf University of M'sila Supervised by Dr. Jilali Tamsawt Grade : conférencier doctorat Number of pages: 106 Electronic file (Cd-Rom * word * PDF) Specialization: Adapted sports physical activity Option : Adapted sports physical activity and health Abstract: The study aimed to know the role of psychological needs among people with mobility disabilities. The study included a sample of (31) specialists. And motor rehabilitation therapists at the of five (05) centers distributed in 03 centers in the municipality of Sidi Issa and two centers at the level of M’sila. After applying the psychological needs scale prepared by the researcher, the results revealed a high value in the degree to which psychological needs contribute to the motor rehabilitation of the disabled. Therefore, this result supports the hypothesis. General search Study title : Psychological needs and their role in motor rehabilitation for the physically disabled In the opinion of motor rehabilitation specialists in some private centers (Msila) Objectives of the study : 1-This study aims to know the most important psychological needs that can be satisfied and their role in motor rehabilitation for disabled people. 2-Determining the level of influence of psychological needs on motor rehabilitation for the physically disabled 3- Revealing the role of psychological needs in motor rehabilitation for the motor disabled 4 - Knowing the basic psychological needs of the physically disabled person in order to understand his behavior and deal with him in appropriate ways 5- Identify psychological needs and work to enhance them in order to raise the level of response in rehabilitation Study problem: What is the role of psychological needs in motor rehabilitation for the physically disabled? hypotheses: A-General hypothesis Psychological needs have a role in motor rehabilitation for the physically disabled. B-Partial hypotheses 1-The needs of independence have a role in the freedom rehabilitation of the physically disabled person 2- Belonging needs have a role in the motor rehabilitation of the physically disabled person 3- Competence needs have a role in the motor rehabilitation of the physically disabled. The method used in the study : descriptive method Tools used in the study: Psychometric questionnaire for psychological needs Keywords - psychological needs - motor rehabilitation - the physically disabled One of the most important results reached by the researcher 01-The degree of independence needs in motor rehabilitation for the disabled is high 02-The degree of belonging needs in motor rehabilitation for the disabled is high 03-The degree of efficiency in motor rehabilitation for the disabled is high recommandations The researcher reached many recommandations, the most important of which is: 1-Working to develop training strategies to develop programs for the stages of motor rehabilitation, guidance and counseling, motor training, vocational employment, and follow-up (and implementing them well in mini-rehabilitation centers 2-Early detection of the psychological needs of individuals in general, especially those with special needs 3-Overcoming the difficulties and problems that stand behind achieving the goals of motor rehabilitation programs for people with disabilities in all motor rehabilitation centers in Algeria. 4- Develop a comprehensive national plan to achieve the maximum benefit from motor rehabilitation centers for the disabled4, their families, and society in general. 5-Interest in developing programs for the physically disabled from the early stage through motor activity exercises -5 6- Suggest similar topics regarding the psychological needs of other variables similar to our program topic
Keywords: الحاجات النفسية; التأهيل الحركي; المعاق حركيا